Дослідження елементів амплітудно-імпульсних і цифрових систем автоматизованого регулювання у програмному середовищі VISSIM - Бодненко, Т. В. (НТУ "ХПІ", 2015)
Стаття присвячена дослідженням елементів амплітудно-імпульсних і цифрових систем автома-тизованого регулювання у програмному середовищі VisSim. Розглянуто стан використання ін-струментальних засобів та середовищ (MathCad, MatLab, VisSim тощо) для спрощення процесу моделювання та дослідження автоматизованих виробничих процесів, визначено напрямки їх ви-користання в сучасних умовах. Використано програмне середовище VisSim для автомазованого регулювання виробничих процесів.

The steep development of microprocessor has led to their widespread use for automatic process control in various spheres of industrial activity. Today designed and mass-produced domestic and foreign manufacturers of a wide variety of technical means of modern computer technology. Nowadays there are a large number of modern tools and environments for process modeling and study of automated production processes. Apart, research items amplitude pulse and digital automated regulation proposed to software environment using VisSim. What has advantages over such tools, as environment MathCad, MatLab and others. Through use of the environment given the opportunity VisSim automated regulation of production processes. VisSim software environment can use as professionals who have deep knowledge in mathematics and programming, and leading experts in programming, create your own blocks with the addition of their library of standard blocks VisSim.
Exploring elements pulse-amplitude and digital automated regulation in the VISSIM environment
Keywords: мікропроцесорні засоби; автоматизовані виробничі процеси; система автоматичного керування; амплітудно-імпульсні моделі; дизайнерські програми; programming environment VisSim; pulse-amplitude computer aided control; computer-aided digital control